2003
DOI: 10.1038/sj.cgt.7700634
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of genetically modified, attenuated Salmonella expressing the E. coli cytosine deaminase gene in refractory cancer patients

Abstract: We performed a pilot trial in refractory cancer patients to investigate the feasibility of intratumoral injection of TAPET-CD, an attenuated Salmonella bacterium expressing the E. coli cytosine deaminase gene. A total of three patients received three dose levels of TAPET-CD (3 Â 10 6 -3 Â 10 7 CFU/m 2 ) via intratumoral injection once every 28 days as long as progression of disease or intolerable toxicity was not observed. From days 4 to 14 of each 28 day cycle, patients also received 5-fluorocytosine (5-FC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
217
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(222 citation statements)
references
References 30 publications
3
217
0
2
Order By: Relevance
“…20,31 For gene therapy in general, a paucity of technologies to monitor events post vector administration to patients represents a block in clinical progression. 32 Indeed, in response to the first gene therapy death, the NIH Recombinant DNA Advisory Committee (RAC) called for better assays to monitor gene delivery.…”
Section: Bacterial-mediated Tumor Therapymentioning
confidence: 99%
“…20,31 For gene therapy in general, a paucity of technologies to monitor events post vector administration to patients represents a block in clinical progression. 32 Indeed, in response to the first gene therapy death, the NIH Recombinant DNA Advisory Committee (RAC) called for better assays to monitor gene delivery.…”
Section: Bacterial-mediated Tumor Therapymentioning
confidence: 99%
“…In spite of great success in a preclinical setting, the application of bacteria for human tumor therapy has not been particularly efficacious, although this approach was well tolerated in most studies. [61][62][63] In light of above-mentioned findings, however, we would suggest that angiogenesis would be a meaningful target for further experimental and clinical studies of bacteria-mediated anti-cancer therapy, particularly if used in conjunction with oncolytic strains of bacteria.…”
Section: Alternative Gene Therapymentioning
confidence: 99%
“…Replicating bacteria have also been briefly tested in clinical trial. 313 Additional measures to modify viral activity by combining treatment with relevant immune modulation therapy (rituximab, enbrel) requires further exploration. Other studies have also shown that modification of the E3 region may minimize viral potency with respect to the durability of selective replication.…”
Section: Other Viral Approachesmentioning
confidence: 99%